ASSOCIATION OF THE ACETYL-COENZYME-A CARBOXYLASE α EXON 1 GENETIC PATTERNS WITH MILK TRAITS IN MAHABADI GOAT - S. Joezy-Shekalgorabi; H. M. Shahr-e-babak; A. Ghorbani (Journal of Animal and Plant Sciences, 2015)
The current study suggests the presence of an association among milk production and genetic polymorphism in the exon I region of Acetyl Coenzyme A Carboxylase α (ACACA) in Iranian indigenous Mahabadi goat. The DNA form 150 does were analysed by PCR-SSCP technique. The results revealed two polymorphic patterns at the exon I region of the ACACA gene on this breed. Each conformation pattern tended to affect milk production, differently (p<0.05). While milk fat and protein percentage and somatic cell score were not statistically associated with these patterns. The result indicated the importance of polymorphism in the exon I region of the ACACA gene as an indicator for marker assisted selection in dairy goat breeds.
Keywords: PCR-SSCP; goat; Acetyl coenzyme A carboxylase α; milk traits